Cardiac fibroelastosis associated with thromboembolism and paresis in a cat - Case report - Carvalho, Thaynara P.; Oliveira, Ayisa R.; Duarte, Mirtha S.; Rezende, Lucas A.; Oliveira, Maira S.; Ribeiro, Beatriz N. T.; Reis, Amanda M. S.; Serakides, Rogéria; Ocarino, Natália M. (Brazilian Journal of Veterinary Pathology, 2019)
A two-year-old, male, non-castrated cat was referred to the veterinary hospital with a three-month history of paresis of the pelvic limbs. Clinical examination revealed a discreet muffling of cardiac sounds and the presence of a degree III/VI holosystolic murmur. The animal was hospitalized and died of cardiorespiratory arrest. The heart had a thickened left ventricular endocardium characterized by the deposition of a fibrous white matter that was firmly adhered to the endocardium and also observed on the epicardium. Renal infarctions and thrombi in the atrium and bifurcation of the aorta were found. Microscopically, in the endocardium of the left ventricular chamber there was a diffuse and disorganized deposition of fibrous connective tissue filled with elastic fibers of varying thickness. In the left ventricular epicardium, the same lesion was observed, but with less extension. Clinical and anatomopathological findings were consistent with primary left ventricular endocardial and left ventricular epicardial fibroelastosis with secondary left ventricular congestive heart failure, thromboembolism and paresis.